P5 Recognizing the disease, treating the patient: a mixed-method evaluation of care for the antiphospholipid syndrome (APS) in the Netherlands. (23rd March 2020) - Haneveld, Mirthe Klein; Lemmen, Caro; Brunekreef, Tammo; Bijl, Marc; Jansen, Gerard; Leeuw, Karina de; Spierings, Julia; Limper, Maarten; ,
Abstract : Purpose: This study aims to gain insight into the care provided to patients with antiphospholipid syndrome (APS) in The Netherlands and to identify areas for improvement from the perspective of both patients and clinicians. Methods: APS care was evaluated using qualitative and quantitative methods. Perspectives on APS care were identified using semi-structured interviews with medical specialists, patient focus groups and a cross-sectional, online patient survey. In order to examine differences in medical practice, medical records were reviewed retrospectively regarding clinical and laboratory manifestations, pharmacological treatment and management of disease in six hospitals throughout The Netherlands. Results: Fourteen interviewed medical specialists, fourteen focus group participants and 79 survey respondents participated in the study. 237 patients were included in medical record review. Only one-third of patients were diagnosed with APS within three months after entering specialist care. Diagnosis and management varied between centres and specialists. Almost 10% of triple positive patients did not receive any treatment at the time of medical record review. Major challenges according to specialists and patients were poor recognition of APS by health care professionals, fragmentation of care and lack of accessible, reliable patient education and psychosocial support. Conclusion: This study describes delayed diagnosis, variability in management strategies and a burden placed on patients to orchestrate their own care in APS care in The Netherlands. Of note, almost 10% of triple positive patients did not receive any treatment, despite this group of patients being at the highest risk of recurrent thrombosis. Acknowledgements: This work was supported by the Arthritis Research and Collaboration Hub (ARCH) Foundation.